EXPERIENCES IN ADAPTING EUROPEAN NETWORK FOR HEALTH TECHNOLOGY ASSESSMENT RAPID REVIEWS TO INFORM LOCAL DECISION MAKING. (9th June 2017) - Macpherson, Karen; Thompson, Lorna
Abstract : Objectives: The Scottish Health Technologies Group (SHTG) produces rapid reviews on nonmedicine technologies to inform advice for decision making in the National Health Service in Scotland (NHSScotland). This study describes our experiences and lessons learned in adapting for NHSScotland two rapid Relative Effectiveness Assessments (REAs) produced as part of the European Network for Health Technology Assessment (EUnetHTA) project to test collaborative preparation and then local adaptation. Methods: The REAs were examined for their relevance to NHSScotland and the feasibility of their adaptation evaluated using a screening toolkit. Some supplementary literature searches were conducted and additional background information on epidemiology and the specific technologies was sought. To inform decision making within Scotland, it was also necessary to identify and review cost-effective analyses. Results: Robust evidence reviews were delivered for NHSScotland. Time saved was less than anticipated, partly due to the need to add in health economic information, and partly because of attempts to supplement and update the EUnetHTA material. The preparation of an accompanying advice statement for NHSScotland enabled the inclusion of local contextual information. Conclusions: Collaborative production and adaptation of HTAs is feasible and would be aided by the inclusion of cost-effectiveness analyses in the original work. Agencies should develop clear processes for adapting such reviews for their context with the focus on selecting appropriate topics for adaptation, avoiding unnecessary supplementation of the original work, and ensuring local ownership of final advice.